Strategi Pengaruh Insentif, Lingkungan Kerja Dan Beban Kerja Terhadap Kinerja Pegawai Melalui Kepuasan Pegawai : Studi Kasus: Dinas PUPR Kabupaten Bogor - Aviva, Munti; Miranda, Agustinus; Derriawan (CV ODIS, 2024)
The purpose of this study is to determine whether there is an influence of Incentives, Work Environment, and Workload both direct and indirect influences on job satisfaction, as well as all of these variables, namely Incentives, Work Environment, Workload, and Performance Satisfaction on Employee Performance, and to find out the right strategy to improve the performance of employees of the Bogor Regency Public Works and Spatial Planning Office (PUPR). The sample used in this study was employees of the Bogor Regency PUPR Office, which was 98 people. Data collection was carried out by distributing questionnaires to 98 employees of the Bogor Regency PUPR Office with data analysis techniques using the Structural Equation Modeling (SEM) method which was processed with the help of SmartPLS software. Where the results of this study are Incentives have no influence on Employee Satisfaction variables, Work Environment has an influence on Employee Satisfaction, Workload has an influence on Employee Satisfaction, Employee Satisfaction has no influence on Employee Performance, Incentives have no influence on Employee Performance, Workload has an influence on Employee Performance, and Work Environment has no influence on Employee Performance